2015
DOI: 10.7567/apex.8.111001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oxygen plasma treatment on the dynamic on-resistance of AlGaN/GaN high-electron-mobility transistors

Abstract: We studied the effects of pre-passivation oxygen plasma treatment of the AlGaN surface on the current collapse of AlGaN/GaN high-electron-mobility transistors (HEMTs). Oxygen plasma-treated devices generally exhibited significantly less dynamic on-resistance (Ron) compared with untreated control devices. We also extended our investigation to HEMTs with a GaN cap layer. Interestingly, after oxygen plasma treatment, we found that GaN-capped HEMTs showed a dynamic Ron behavior that was essentially similar to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…In addition, the on resistance, R on , of the devices can be obtained through the pulse‐IV curves, and the values of R on of the four samples were 6.1, 5.1, 6.08, and 7.4 mΩ mm, respectively. Ron of oxygen plasma treated devices had not significantly deteriorated . Therefore, devices with ICP based oxygen plasma treatment showed good switching characteristics …”
Section: Resultsmentioning
confidence: 95%
“…In addition, the on resistance, R on , of the devices can be obtained through the pulse‐IV curves, and the values of R on of the four samples were 6.1, 5.1, 6.08, and 7.4 mΩ mm, respectively. Ron of oxygen plasma treated devices had not significantly deteriorated . Therefore, devices with ICP based oxygen plasma treatment showed good switching characteristics …”
Section: Resultsmentioning
confidence: 95%
“…It was suggested that using simultaneously two different approaches in mitigating current collapse did not necessarily guarantee a cumulative effect. 72) To put it explicitly, it was found that the GaN cap layer contributed no further reduction in current collapse in the devices already subjected to O 2 plasma treatment. Another report described a systematic investigation of the combined effect of O 2 plasma treatment and FP structure on current collapse.…”
Section: Effect Of Field Platementioning
confidence: 99%
“…[69][70][71] Recently, a significant reduction in current collapse has been demonstrated for O 2 plasma-treated AlGaN=GaN HEMTs as evidenced by highly reduced NDR in these devices over that of a reference device. 72) The AlGaN surface of the devices was exposed to O 2 plasma with an RF power of 100 W and an exposure time of 60 s. This was carried out prior to a SiN passivation step of the fabrication process shown in Fig. 1.…”
Section: Effect Of O 2 Plasma Treatment and Gan Capmentioning
confidence: 99%
“…For instance, we have found out that the GaN cap layer contributes no further reduction of current collapse in the devices already subjected to oxygen (O 2 ) plasma treatment. 28) It follows that careful consideration should be taken in choosing what schemes to combine for achieving reduced current collapse. In this work, we demonstrate for the first time highly suppressed current collapse in AlGaN=GaN high-electron-mobility transistors (HEMTs) by combined application of pre-passivation O 2 plasma treatment and FP structures.…”
Section: Introductionmentioning
confidence: 99%